Niobium-hafnium alloy material and preparation method and application thereof

By using niobium hafnium alloy materials in high-pressure electrostatic air purification equipment, the solid solution strengthening and pre-alloying technology of hafnium and niobium, the problems of poor processing performance and weak oxidation resistance of metal hafnium are solved, and a higher service life and lower risk of oxidation and ablation are achieved.

CN119843129APending Publication Date: 2025-04-18韩伴祥
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510078722.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In existing high-voltage electrostatic air purification equipment, metal hafnium has poor processing performance and weak oxidation resistance, resulting in a short service life, which limits its application in the field of high-voltage electrostatic purification.

Method used

Using niobium hafnium alloy material, the continuous mutual dissolution of hafnium and niobium in the liquid solid state is formed to form a solid solution, improving processing performance and oxidation resistance. At the same time, the pre-prepared intermediate alloy wire of zirconium and scandium is wound on the niobium rod to deposit metal hafnium, and the volatile scandium is closed through the pre-alloyation process, reducing its volatile loss during the smelting alloy process and ensuring uniform alloy composition.

Benefits of technology

It significantly improves the processing performance and oxidation resistance of metal hafnium, extends the service life, and reduces the oxidation ablation and wire breakage caused by high-voltage electrostatic spark discharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843129A_ABST
    Figure CN119843129A_ABST
Patent Text Reader

Abstract

The invention provides a niobium-hafnium alloy material and a preparation method and application thereof, and belongs to the field of nonferrous metal materials. The preparation method of the niobium-hafnium alloy material comprises the following steps that a scandium-zirconium alloy wire or a rare earth-zirconium alloy wire is wound on a metal niobium rod, the metal niobium rod is electrified and heated to generate a high-temperature area, and metal hafnium is placed in a low-temperature area; the iodine reacts with metal hafnium in the low-temperature area to generate hafnium iodide, the generated hafnium iodide is diffused to the high-temperature area and decomposed into metal hafnium on the surface of the niobium rod wound with the alloy wire, and a scandium-zirconium-niobium-niobium metal rod with a scandium-zirconium-niobium rod or a rare earth zirconium-niobium rod as the center and with the metal hafnium wrapped on the surface or a rare earth zirconium-niobium-hafnium metal rod with the metal hafnium wrapped on the surface is formed; raising the temperature of the metal niobium rod and keeping constant temperature for a certain time; and then smelting is conducted, and the niobium-hafnium alloy material is obtained. According to the prepared niobium-hafnium alloy material, the processing performance of metal hafnium is effectively improved, the internal and surface defects of the alloy are reduced, the high-voltage electrostatic oxidation corrosion resistance is improved, and the service life of equipment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nonferrous metal materials, in particular to a niobium-hafnium alloy material and a preparation method and application thereof. Background Art

[0002] At present, metal tungsten is the main material for the discharge electrode of high-voltage electrostatic air purification equipment. The tungsten electrode corona discharges and generates ion wind, which plays a role in dust removal and air purification. The melting point of metal tungsten is 3410℃, the electron work function is 4.5eV, it has strong antioxidant ability and long life; but its disadvantages are small ventilation volume and low purification efficiency. In comparison, the melting point of metal hafnium is 2230℃, and the electron work function is 3.5eV. As the discharge electrode of electrostatic air purification equipment, it generates large air volume and high purification efficiency, but the anti-oxidation corrosion ability of metal hafnium is much lower than that of metal tungsten, and the service life is short. In addition, the processing performance of metal hafnium is poor, and there are many processing defects inside and on the surface of the electrode. High-voltage static electricity will continuously discharge at the defects, resulting in oxidation and ablation, which will cause the electrode to break, further shortening its service life, limiting its application in the field of high-voltage electrostatic purification.

[0003] Therefore, it is of great significance to develop a hafnium alloy material with good processing performance, strong oxidation resistance and long service life as a corona discharge electrode on high-voltage electrostatic purification equipment. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention provides a niobium-hafnium alloy material and a preparation method and application thereof.

[0005] A niobium-hafnium alloy material comprises the following components in percentage by mass: 0.05-9.5% niobium, 0.05-6.5% zirconium, ≤0.9% scandium, and the total content of inevitable impurities ≤0.5%, wherein, among the inevitable impurities, the content of a single impurity does not exceed 0.05%, and the balance is hafnium.

[0006] Alternatively, the invention comprises the following components in percentage by mass: 0.05-9.5% niobium, 0.05-4.5% zirconium, and ≤1.5% rare earth, wherein the rare earth metal is one or more of scandium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, yttrium, and lutetium, and the total content of inevitable impurities is ≤0.5%, wherein, among the inevitable impurities, the content of a single impurity does not exceed 0.05%, and the balance is hafnium.

[0007] A method for preparing a niobium-hafnium alloy material, the method is used to obtain the niobium-hafnium alloy material as described above, and comprises the following steps:

[0008] S1, placing metal hafnium around the inner wall of a preset furnace body, winding a scandium-zirconium alloy wire or a rare earth zirconium alloy wire onto a metal niobium rod, wherein the metal niobium rod is located in the preset furnace body; evacuating the preset furnace body and adding iodine; electrically heating the metal niobium rod to generate a high temperature zone, and the inner wall of the preset furnace body is a low temperature zone relative to the high temperature zone; in the low temperature zone, metal hafnium and iodine generate hafnium iodide and diffuse to the high temperature zone; the surface of the metal niobium rod is decomposed into metal hafnium, and a scandium-zirconium-niobium-hafnium metal rod with the scandium-zirconium-niobium rod as the center and the metal hafnium wrapped on the surface is formed, or a rare earth-zirconium-niobium-hafnium metal rod with the rare earth-zirconium-niobium rod as the center and the metal hafnium wrapped on the surface is formed;

[0009] S2, raising the temperature of the scandium-zirconium-niobium-hafnium metal rod or the rare earth zirconium-niobium-hafnium metal rod and maintaining the temperature for a preset constant time;

[0010] S3, smelting the scandium-zirconium-niobium-hafnium metal rod or the rare earth-zirconium-niobium-hafnium metal rod to obtain the niobium-hafnium alloy material containing scandium-zirconium or rare earth-zirconium.

[0011] An application based on niobium and hafnium alloy materials. The niobium and hafnium alloy materials or the niobium and hafnium alloy materials obtained by the above-mentioned niobium and hafnium alloy material preparation method are used in high-voltage electrostatic air purification equipment or high-voltage electrostatic air purification components in fresh air systems.

[0012] Compared with the prior art, the niobium-hafnium alloy material and the preparation method and application thereof provided by the present invention have the following beneficial effects:

[0013] 1) The niobium-hafnium alloy material provided by the present invention is obtained by continuous dissolution of hafnium and niobium in liquid and solid states (see the specification Figure 4 ), which plays a role of solid solution strengthening, effectively improving the processing performance of metal hafnium and enhancing its antioxidant properties.

[0014] 2) Rare earth metals can be used as additives to refine alloy grains and improve organizational structure and performance. However, rare earth metals generally have low melting points and high vapor pressures. When rare earth metals and high melting point metals form alloys, the volatilization loss is large and the composition is difficult to control. Take scandium metal as an example. The melting point of scandium metal is 1541℃, the density is 2.99g / cm3, and the vapor pressure of scandium is 91.3Pa at around 2000K. When directly smelted with hafnium and niobium to form an alloy, the volatilization loss of scandium metal is large and the alloy composition is difficult to control. The melting point of zirconium metal is 1852℃, which is close to that of scandium metal. Zirconium metal and scandium (see instructions) Figure 2 ), zirconium and niobium (see instructions Figure 3), zirconium and hafnium can be continuously soluble in each other in liquid and solid. The present invention uses a pre-prepared intermediate alloy wire of zirconium and scandium, which is wound on a metal niobium rod, and then metal hafnium is deposited on it, so that the volatile metal scandium is sealed inside, and the scandium-zirconium alloy wire is pre-alloyed with the internal niobium rod and the metal hafnium covered on the outside by raising the temperature and keeping it constant for a period of time to form a pre-alloyed rod (see the attached figure of the specification). Fig.10 ). During the pre-alloying process, scandium, zirconium, niobium and hafnium are mutually dissolved and infiltrated, forming a partial alloy state before melting. When the metals are melted and alloyed, the metals can be quickly and effectively fused, which greatly reduces the volatilization loss of metal scandium during the melting and alloying process, and the alloy composition is uniform.

[0015] 3) In the present invention, scandium and hafnium (see specification Figure 1 ) can be continuously dissolved in both liquid and solid states. Adding scandium metal can refine hafnium grains, improve organizational structure, increase tensile strength, and reduce processing defects inside and on the surface of the wire. The solid solution strengthening effect of niobium metal effectively improves the processing performance of hafnium metal and improves its anti-oxidation performance. As a discharge electrode for high-voltage electrostatic air purification equipment, the reduction of processing defects effectively reduces the phenomenon of oxidation, ablation and wire breakage caused by high-voltage electrostatic spark discharge, and the enhanced anti-oxidation performance increases the service life of the discharge electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The Hf-Sc phase diagram of hafnium and scandium in liquid and solid states with continuous miscibility;

[0017] Figure 2 The phase diagram of Zr-Sc system with continuous dissolution of zirconium and scandium in liquid and solid states;

[0018] Figure 3 The phase diagram of Zr-Nb system with continuous mutual solubility of zirconium and niobium at high temperature and in solid and liquid state;

[0019] Figure 4 The Hf-Nb phase diagram for producing a body-centered cubic continuous solid solution between high-temperature hafnium and niobium;

[0020] Figure 5 This is a SEM test image of the scandium-zirconium-niobium-hafnium alloy wire at a magnification of 100 μm in Application Example 3 of the present invention;

[0021] Figure 6 This is a SEM test image of the scandium-zirconium-niobium-hafnium alloy wire in Application Example 5 of the present invention at a magnification of 100 μm;

[0022] Figure 7 This is a SEM test image of the comparative example 99.9% hafnium wire at a magnification of 100 μm;

[0023] Figure 8 This is a schematic diagram of the structure of the high-voltage electrostatic purification equipment in Application Example 1 of the present invention;

[0024] Fig. 9 This is a schematic diagram of the angle between the scandium-zirconium-niobium-hafnium alloy wire of the present invention and the integrated electrode when the wire is used as a discharge electrode;

[0025] Fig.10 It is a schematic diagram of the scandium-zirconium-niobium-hafnium pre-alloyed rod or the rare earth zirconium-niobium-hafnium pre-alloyed rod of the present invention;

[0026] Fig.11 It is a schematic diagram of a device for preparing the scandium-zirconium-niobium-hafnium pre-alloyed rod or the rare earth zirconium-niobium-hafnium pre-alloyed rod of the present invention;

[0027] The symbols in the drawings of the specification are as follows:

[0028] 1. Alloy wire; 2. Insulation frame; 3. Dust collecting plate; 4. Insulation frame; 5. Pre-alloyed rod with metal hafnium outer layer; 6. Pre-alloyed rod with metal zirconium-scandium alloy middle layer; 7. Pre-alloyed rod with metal niobium inner layer; 8. Metal hafnium; 9. Scandium-zirconium alloy wire / rare earth zirconium alloy wire; 10. Metal niobium rod. DETAILED DESCRIPTION

[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] The invention provides a niobium-hafnium alloy material, comprising the following components in percentage by mass: 0.05-9.5% niobium, 0.05-6.5% zirconium, ≤0.9% scandium, the total content of inevitable impurities ≤0.5%, the content of a single impurity not exceeding 0.05%, and the balance being hafnium.

[0031] Wherein, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0032] The mass percentage of niobium is 0.05-9.5%, preferably 0.05-6.5%, more preferably 0.1-5%, and even more preferably 0.2-3%.

[0033] The mass percentage of the metal scandium is scandium ≤ 0.9%, preferably 0.01 to 0.6%, more preferably 0.05 to 0.4%, and even more preferably 0.05 to 0.3%.

[0034] The mass percentage of the metal zirconium is 0.05-6.5%, preferably 0.05-5%, more preferably 0.1-3%, and even more preferably 0.1-1%.

[0035] The present invention provides a method for preparing the niobium-hafnium alloy material described in the above technical solution, comprising the following steps:

[0036] 1) Placing metal hafnium around the inner wall of a preset furnace;

[0037] 2) Winding a scandium-zirconium alloy wire in a required ratio onto a metal niobium rod;

[0038] 3) After the furnace body is evacuated, iodine is added; the metal niobium rod is electrically heated to generate a high temperature zone, and iodine reacts with metal hafnium in the low temperature zone to generate hafnium iodide, which diffuses into the high temperature zone and decomposes into metal hafnium on the surface of the niobium rod wound with the scandium zirconium wire, thereby forming a scandium zirconium niobium hafnium metal rod with the scandium zirconium niobium rod as the center and the metal hafnium wrapped on the surface;

[0039] 3) raising the temperature of the scandium-zirconium-niobium-hafnium metal rod and keeping the temperature constant for a certain period of time;

[0040] 4) Smelting the scandium-zirconium-niobium-hafnium metal rod to obtain a scandium-zirconium-niobium-hafnium alloy material.

[0041] Among them, the temperature of the high temperature zone is 950-1350°C, preferably 1000-1250°C, and more preferably 1150°C; the temperature of the low temperature zone is 250-350°C; the constant temperature is 1500-1900°C, preferably 280-320°C, and more preferably 290°C; the constant temperature time is 0.5-5 hours.

[0042] Iodine reacts with metal hafnium in a low temperature region to generate hafnium iodide, and the hafnium iodide diffuses to the high temperature surface of the niobium rod wound with the scandium zirconium wire and decomposes into metal hafnium, thereby forming a scandium zirconium niobium hafnium metal rod with the scandium zirconium niobium rod as the center and the metal hafnium wrapped on the surface;

[0043] The obtained scandium-zirconium-niobium-hafnium metal rod is heated and kept at a constant temperature for a certain period of time. In the present invention, the constant temperature is 1500-1900° C., preferably 1540-1850° C., and the constant temperature time is 0.5-5 hours, preferably 3-4 hours.

[0044] Metal hafnium has a strong affinity for oxygen, and alloy melting needs to be carried out under high vacuum conditions. Under such conditions, the volatilization loss of metal scandium is large, and the density difference between metal hafnium and metal scandium is also large, making it difficult to homogenize the alloy. The present invention uses a pre-prepared intermediate alloy wire of zirconium and scandium, which is wound on a metal niobium rod, and then metal hafnium is deposited on it, so that the volatile metal scandium is sealed inside, and the scandium-zirconium alloy wire is pre-alloyed with the internal niobium rod and the metal hafnium covered on the outside by raising the temperature and keeping it constant for a period of time, so that scandium, zirconium, hafnium, and niobium penetrate each other during melting. When melting the alloy, the characteristics of scandium, zirconium, hafnium, and niobium that can be continuously dissolved in liquid and solid states enable the pre-alloyed metals to quickly fuse with each other, effectively solving the above technical problems.

[0045] The present invention provides another niobium-hafnium alloy material, comprising the following components in percentage by mass: 0.05-9.5% niobium, 0.05-4.5% zirconium, ≤1.5% rare earth, ≤0.5% total content of inevitable impurities, ≤0.5% content of a single impurity, and the balance being hafnium.

[0046] Wherein, unless otherwise specified, the required raw materials for preparation are all commercially available products well known to those skilled in the art.

[0047] The mass percentage of niobium is 0.05-9.5%, preferably 0.05-6.5%, more preferably 0.1-5%, and even more preferably 0.2-3%.

[0048] The mass percentage of the rare earth metal is rare earth ≤ 1.5%, preferably 0.01 to 0.9%, more preferably 0.05 to 0.5%, and even more preferably 0.05 to 0.3%.

[0049] The rare earth is one or more of scandium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, yttrium, and lutetium, preferably scandium, yttrium, gadolinium, terbium, and lutetium, more preferably yttrium and scandium, and more preferably scandium.

[0050] The mass percentage of the metal zirconium is 0.05-4.5%, preferably 0.05-3%, more preferably 0.1-3%, and even more preferably 0.1-1%.

[0051] The present invention provides a method for preparing the niobium-hafnium alloy material described in the above technical solution, comprising the following steps:

[0052] 1) Winding a rare earth zirconium alloy wire according to a required ratio onto a metal niobium rod;

[0053] 2) the metal niobium rod is electrically heated to generate a high temperature zone, the metal hafnium is placed in a low temperature zone, iodine reacts with the metal hafnium in the low temperature zone to generate hafnium iodide which diffuses to the high temperature zone and decomposes into metal hafnium on the surface of the niobium rod wound with the rare earth zirconium wire, thereby forming a rare earth zirconium niobium hafnium metal rod with the rare earth zirconium niobium rod as the center and the metal hafnium wrapped on the surface;

[0054] 3) raising the temperature of the rare earth zirconium, niobium and hafnium metal rod and maintaining the temperature constant for a certain period of time;

[0055] 4) Smelting the rare earth zirconium niobium hafnium metal rod to obtain a rare earth zirconium niobium hafnium alloy material.

[0056] Among them, the temperature of the high temperature zone is 950-1350°C, preferably 1000-1250°C, and more preferably 1150°C; the temperature of the low temperature zone is 250-350°C, preferably 280-320°C, and more preferably 290°C; the constant temperature is 1500-1900°C, and the constant temperature time is 0.5-5 hours.

[0057] Iodine reacts with metal hafnium in a low temperature region to generate hafnium iodide, and the hafnium iodide diffuses to the high temperature surface of the niobium rod wound with the rare earth zirconium wire and decomposes into metal hafnium, thereby forming a rare earth zirconium niobium hafnium metal rod with the rare earth zirconium niobium rod as the center and the metal hafnium wrapped on the surface;

[0058] The obtained rare earth zirconium niobium hafnium metal rod is heated and kept at a constant temperature for a certain period of time. In the present invention, the constant temperature is 1500-1900° C., preferably 1540-1850° C., and the constant temperature time is 0.5-5 hours, preferably 3-4 hours.

[0059] Metal hafnium has a strong affinity for oxygen, and alloy melting needs to be carried out under relatively high vacuum conditions. Under such conditions, the volatilization loss of rare earth metals is large, and the density difference between metal hafnium and rare earth metals is also large, making it difficult to homogenize the alloy. The present invention uses a pre-prepared intermediate alloy wire of zirconium and rare earth metals, which is wound on a metal niobium rod, and then metal hafnium is deposited on it, so that the volatile rare earth metal is sealed inside, and the rare earth zirconium alloy wire is pre-alloyed with the internal niobium rod and the metal hafnium covered on the outside by raising the temperature and keeping it constant for a period of time, so that the rare earth, zirconium, hafnium, and niobium penetrate each other. When melting the alloy, the characteristics of zirconium, hafnium, and niobium that can be continuously dissolved in liquid and solid states enable the pre-alloyed metals to quickly fuse with each other, effectively solving the above technical problems.

[0060] It should be noted that the present invention has no special limitation on the metal hafnium, and those skilled in the art can select it according to actual needs, for example: hafnium sponge, metal hafnium chips, metal hafnium blocks; in the embodiment of the present invention, the metal hafnium is preferably in the form of nuclear grade hafnium sponge.

[0061] The present invention has no special limitation on the smelting equipment used for the hafnium-niobium alloy, and those skilled in the art can select it according to actual needs, for example: vacuum induction melting furnace, vacuum suspension melting furnace, vacuum arc melting furnace and vacuum electron beam melting furnace.

[0062] The present invention has no special limitation on the method and conditions for the surface pretreatment of the niobium-hafnium-gold rod, and those skilled in the art may select the method and conditions according to actual needs, for example, at least one of ultrasonic cleaning, pickling, and turning.

[0063] The present invention provides the use of the niobium-hafnium alloy material described in the above technical solution or the niobium-hafnium alloy material prepared by the preparation method of the niobium-hafnium alloy material described in the above technical solution in high-voltage electrostatic air purification equipment.

[0064] In the present invention, the niobium-hafnium alloy material is preferably used as a corona discharge electrode in a high-voltage electrostatic air purification device in the form of niobium-hafnium alloy wire.

[0065] In the present invention, the diameter of the niobium-hafnium alloy wire is preferably 0.2-1.0 mm, more preferably 0.25-0.55 mm, and more preferably 0.3-0.5 mm; the distance between the niobium-hafnium alloy wire and the dust collecting electrode in the high-voltage electrostatic air purification equipment is preferably 30-100 mm, more preferably 35-60 mm, and more preferably 40-50 mm; the niobium-hafnium alloy wire is connected to the positive or negative electrode of the high-voltage electrostatic power supply in the high-voltage electrostatic air purification equipment.

[0066] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0067] Example 1

[0068] (1) A 1 mm diameter scandium-zirconium alloy wire is uniformly wound around a 4 mm diameter metal niobium rod according to the mass percentage of scandium 0.4%, zirconium 4%, niobium 6%, and the balance hafnium.

[0069] (2) placing nuclear-grade hafnium sponge around the wall of a vacuum reactor, connecting the niobium rod in step (1) to a heating power source, evacuating to 5×103 Pa, closing the vacuum valve to form a closed space, then adding iodine, connecting the power source to heat the niobium rod, and controlling the temperature of the low-temperature zone of the furnace wall to 290° C. and the temperature of the high-temperature zone formed by the niobium rod to 1150° C., so that iodine reacts with the hafnium sponge to form hafnium iodide, and the hafnium iodide diffuses on the niobium rod wound with the scandium-zirconium alloy wire and decomposes to form metallic hafnium; maintaining the reaction for 23 hours to form a scandium-zirconium-niobium-hafnium metal rod with a niobium rod in the center, scandium-zirconium in the middle, and metallic hafnium on the outer layer.

[0070] (3) The scandium-zirconium-niobium-hafnium metal rod in step (2) is heated to 1750° C. and kept at the constant temperature for 3 hours.

[0071] (4) The surface of the scandium-zirconium-niobium-hafnium alloy rod in step (3) is ultrasonically cleaned with pure water, dried at 85° C., and then smelted to obtain a scandium-zirconium-niobium-hafnium alloy ingot.

[0072] Example 2

[0073] (1) A 1 mm diameter scandium-zirconium alloy wire is uniformly wound around a 4 mm diameter metal niobium rod according to the mass percentage of scandium 0.2%, zirconium 1%, niobium 2%, and the balance hafnium.

[0074] (2) placing nuclear-grade hafnium sponge around the wall of a vacuum reactor, connecting the niobium rod in step (1) to a heating power source, evacuating to 5×103 Pa, closing the vacuum valve to form a closed space, then adding iodine, connecting the power source to heat the niobium rod, and controlling the temperature of the low-temperature zone of the furnace wall to 290° C. and the temperature of the high-temperature zone formed by the niobium rod to 1150° C., so that iodine reacts with the hafnium sponge to form hafnium iodide, and the hafnium iodide diffuses on the niobium rod wound with the scandium-zirconium alloy wire and decomposes to form metallic hafnium; maintaining the reaction for 31 hours to form a scandium-zirconium-niobium-hafnium metal rod with a niobium rod in the center, scandium-zirconium in the middle, and metallic hafnium on the outer layer.

[0075] (3) The scandium-zirconium-niobium-hafnium metal rod in step (2) is heated to 1750° C. and kept at the constant temperature for 3 hours.

[0076] (4) The surface of the scandium-zirconium-niobium-hafnium alloy rod in step (3) is ultrasonically cleaned with pure water, and then dried at 85° C., and then smelted to obtain a scandium-zirconium-niobium-hafnium alloy ingot.

[0077] Example 3

[0078] (1) A 1 mm diameter scandium-zirconium alloy wire is uniformly wound around a 4 mm diameter metal niobium rod according to the mass percentage of scandium 0.1%, zirconium 0.5%, niobium 1%, and the balance hafnium.

[0079] (2) placing nuclear-grade hafnium sponge around the wall of a vacuum reactor, connecting the niobium rod in step (1) to a heating power source, evacuating to 5×103 Pa, closing the vacuum valve to form a closed space, then adding iodine, connecting the power source to heat the niobium rod, and controlling the temperature of the low-temperature zone of the furnace wall to 290° C. and the temperature of the high-temperature zone formed by the niobium rod to 1150° C., so that iodine reacts with the hafnium sponge to form hafnium iodide, and the hafnium iodide diffuses on the niobium rod wound with the scandium-zirconium alloy wire and decomposes to form metallic hafnium; maintaining the reaction for 54 hours to form a scandium-zirconium-niobium-hafnium metal rod with a niobium rod in the center, scandium-zirconium in the middle, and metallic hafnium on the outer layer.

[0080] (3) The scandium-zirconium-niobium-hafnium metal rod in step (2) is heated to 1750° C. and kept at the constant temperature for 3 hours.

[0081] (4) The surface of the scandium-zirconium-niobium-hafnium alloy rod in step (3) is ultrasonically cleaned with pure water, and then dried at 85° C., and then smelted to obtain a scandium-zirconium-niobium-hafnium alloy ingot.

[0082] Example 4

[0083] (1) According to the mass percentage of scandium 0.05%, zirconium 0.3%, niobium 0.5%, and the balance hafnium, the diameter

[0084] 1mm scandium-zirconium alloy wire is evenly wound on a 4mm diameter metal niobium rod.

[0085] (2) placing nuclear-grade hafnium sponge around the wall of a vacuum reactor, connecting the niobium rod in step (1) to a heating power source, evacuating to 5×103 Pa, closing the vacuum valve to form a closed space, then adding iodine, connecting the power source to heat the niobium rod, and controlling the temperature of the low-temperature zone of the furnace wall to 290° C. and the temperature of the high-temperature zone formed by the niobium rod to 1150° C., so that iodine reacts with the hafnium sponge to form hafnium iodide, and the hafnium iodide diffuses on the niobium rod wound with the scandium-zirconium alloy wire and decomposes to form metallic hafnium; maintaining the reaction for 77 hours to form a scandium-zirconium-niobium-hafnium metal rod with a niobium rod in the center, scandium-zirconium in the middle, and metallic hafnium on the outer layer.

[0086] (3) The scandium-zirconium-niobium-hafnium metal rod in step (2) is heated to 1750° C. and kept at the constant temperature for 3 hours.

[0087] (4) The surface of the scandium-zirconium-niobium-hafnium alloy rod in step (3) is ultrasonically cleaned with pure water, and then dried at 85° C., and then smelted to obtain a scandium-zirconium-niobium-hafnium alloy ingot.

[0088] Example 5

[0089] (1) According to the mass percentage of scandium 0%, zirconium 0.5%, niobium 1%, and the balance hafnium, a 1mm diameter

[0090] The zirconium wire is evenly wound on a 4mm diameter niobium metal rod.

[0091] (2) placing nuclear-grade hafnium sponge around the wall of a vacuum reactor, connecting the niobium rod in step (1) to a heating power source, evacuating to 5×103 Pa, closing the vacuum valve to form a closed space, then adding iodine, connecting the power source to heat the niobium rod, and controlling the temperature of the low-temperature zone of the furnace wall to 290° C. and the temperature of the high-temperature zone formed by the niobium rod to 1150° C., so that iodine reacts with the hafnium sponge to form hafnium iodide, and the hafnium iodide diffuses on the niobium rod wrapped with zirconium wire and decomposes to form metallic hafnium; maintaining the reaction for 54 hours to form a zirconium-niobium-hafnium metal rod with a niobium rod in the center, zirconium in the middle, and metallic hafnium on the outer layer.

[0092] (3) The zirconium, niobium and hafnium metal rods in step (2) are heated to 1850° C. and kept at this temperature for 3 hours.

[0093] (4) The surface of the zirconium niobium hafnium alloy rod in step (3) is ultrasonically cleaned with pure water, and then dried at 85° C., and then smelted to obtain a zirconium niobium hafnium alloy ingot.

[0094] Application Example 1

[0095] The scandium-zirconium-niobium-hafnium alloy prepared in Example 1 was processed into a 2000 mm diameter scandium-zirconium-niobium-hafnium alloy wire used as a discharge electrode of a high-voltage electrostatic air purifier and connected to the positive electrode of a high-voltage electrostatic power supply; four stainless steel sheets with a width of 50 mm and a length of 500 mm were used as dust collecting sheets. The steel sheets were parallel to each other and the distance between the steel sheets was 50 mm. The steel sheets were fixed on an insulating bracket and connected to the negative electrode of the high-voltage power supply; the scandium-zirconium-niobium-hafnium alloy wire was 5 mm away from the adjacent steel sheet, and the scandium-zirconium-niobium-hafnium alloy wire was parallel to the edge of the steel sheet, such as Figure 8 shown.

[0096] Application Example 2

[0097] The only difference from Application Example 1 is that the scandium-zirconium-niobium-hafnium alloy obtained in Example 2 is used, and other conditions remain unchanged.

[0098] Application Example 3

[0099] The only difference from Application Example 1 is that the scandium-zirconium-niobium-hafnium alloy obtained in Example 3 is used, and other conditions remain unchanged.

[0100] Application Example 4

[0101] The only difference from Application Example 1 is that the scandium-zirconium-niobium-hafnium alloy obtained in Example 4 is used, and other conditions remain unchanged.

[0102] Application 5 cases

[0103] The only difference from Application Example 1 is that the zirconium-niobium-hafnium alloy obtained in Example 5 is used, and other conditions remain unchanged.

[0104] Comparative application example 1

[0105] The only difference from Application Example 1 is that 99.9% pure hafnium metal wire is used as the discharge electrode of the high-voltage electrostatic air purifier, and other conditions remain unchanged.

[0106] Performance Testing

[0107] The high-voltage electrostatic purification equipment described in Application Examples 1 to 5 and Comparative Application Example 1 was connected to a 32 kV DC voltage, and the alloy wire was weighed after continuous operation for 90 days, and the oxidation loss of the sample was calculated according to the weight loss method formula. The results are shown in Table 1.

[0108] Table 1 Performance test results of application examples 1 to 5 and comparative application example 1

[0109]

[0110] By comparing the data in Table 1, it can be seen that when the niobium-hafnium alloy material prepared in the present invention is used as a discharge electrode material for a high-voltage electrostatic air purifier, the resistance to high-voltage electrostatic oxidation corrosion is significantly improved compared to pure metal hafnium with a purity of 99.9%.

[0111] The zirconium-niobium-hafnium alloy wire described in Example 5 and the 99.9% pure metal hafnium wire described in Comparative Application Example 1 were subjected to SEM testing. The results obtained were Figure 6 and Figure 7 shown; through Figure 6 , Figure 7 It can be seen from the comparison that 99.9% pure metal hafnium wire has obvious microcrack defects inside. In a high-voltage static environment, microcracks are prone to produce tip spark discharge, which accelerates the oxidation corrosion rate. However, the zirconium-niobium-hafnium alloy wire prepared by the preparation method provided by the present invention improves the processing performance due to the addition of metal niobium, which effectively inhibits the generation of microcracks. The corresponding zirconium-niobium-hafnium alloy wire described in Example 3 and the scandium-zirconium-niobium-hafnium alloy wire described in Application Example 5 were subjected to SEM testing, and the results obtained were Figure 5 and Figure 6 shown; through Figure 5 , Figure 6 By comparison, it can be seen that a trace amount of scandium can refine the grains and make the internal structure uniform, thereby greatly improving the service life.

[0112] The above is an explanation of the technical solution of the present invention to help understand the present invention; however, the implementation mode of the present invention is not limited to the above-mentioned embodiments, and any changes, modifications, substitutions, combinations, and simplifications made without departing from the principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A niobium-hafnium alloy material, characterized in that: Comprising the following components in percentage by mass: 0.05-9.5% niobium, 0.05-6.5% zirconium, ≤0.9% scandium, and the total content of inevitable impurities ≤0.5%, wherein, among the inevitable impurities, the content of a single impurity does not exceed 0.05%, and the balance is hafnium; Alternatively, the invention comprises the following components in percentage by mass: 0.05-9.5% niobium, 0.05-4.5% zirconium, and ≤1.5% rare earth, wherein the rare earth metal is one or more of scandium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, yttrium, and lutetium, and the total content of inevitable impurities is ≤0.5%, wherein, among the inevitable impurities, the content of a single impurity does not exceed 0.05%, and the balance is hafnium.

2. A method for preparing a niobium-hafnium alloy material, characterized in that: The preparation method is used to obtain the niobium-hafnium alloy material as claimed in claim 1, and comprises the following steps: S1, placing metal hafnium around the inner wall of a preset furnace body, winding a scandium-zirconium alloy wire or a rare earth zirconium alloy wire onto a metal niobium rod, wherein the metal niobium rod is located in the preset furnace body; evacuating the preset furnace body and adding iodine; electrically heating the metal niobium rod to generate a high temperature zone, and the inner wall of the preset furnace body is a low temperature zone relative to the high temperature zone; in the low temperature zone, metal hafnium and iodine generate hafnium iodide and diffuse to the high temperature zone; the surface of the metal niobium rod is decomposed into metal hafnium, and a scandium-zirconium-niobium-hafnium metal rod with the scandium-zirconium-niobium rod as the center and the metal hafnium wrapped on the surface is formed, or a rare earth-zirconium-niobium-hafnium metal rod with the rare earth-zirconium-niobium rod as the center and the metal hafnium wrapped on the surface is formed; S2, raising the temperature of the scandium-zirconium-niobium-hafnium metal rod or the rare earth zirconium-niobium-hafnium metal rod and maintaining the temperature for a preset constant time; S3, smelting the scandium-zirconium-niobium-hafnium metal rod or the rare earth-zirconium-niobium-hafnium metal rod to obtain the niobium-hafnium alloy material containing scandium-zirconium or rare earth-zirconium.

3. The method for preparing the niobium-hafnium alloy material according to claim 2, characterized in that: The temperature of the high temperature zone is 950-1350°C, and the temperature of the low temperature zone is 250-350°C.

4. The method for preparing the niobium-hafnium alloy material according to claim 2, characterized in that: The constant temperature of the scandium-zirconium-niobium-hafnium metal rod is 1500-1900° C., and the constant temperature time is 0.5-5 hours.

5. An application based on niobium-hafnium alloy material, characterized in that: The niobium-hafnium alloy material according to claim 1 or the niobium-hafnium alloy material obtained by the method for preparing the niobium-hafnium alloy material according to any one of claims 2 to 4 is used in a high-voltage electrostatic air purification device or a high-voltage electrostatic air purification component in a fresh air system.

6. The use of niobium-hafnium alloy material according to claim 5, characterized in that: The niobium-hafnium alloy material is used as a discharge electrode in the high-voltage electrostatic air purification device or the high-voltage electrostatic air purification component in the fresh air system in the form of niobium-hafnium alloy wire; Alternatively, the niobium-hafnium alloy material is used as a discharge electrode in the high-voltage electrostatic air purification device or the high-voltage electrostatic air purification component in the fresh air system in the form of a niobium-hafnium alloy sheet.

7. The use of niobium-hafnium alloy material according to claim 6, characterized in that: The diameter of the niobium-hafnium alloy wire is 0.1-2 mm, and the distance between the niobium-hafnium alloy wire and the dust collecting electrode in the high-voltage electrostatic air purification device is 15-200 mm; the niobium-hafnium alloy wire is connected to the positive electrode or the negative electrode of the high-voltage electrostatic power supply in the high-voltage electrostatic air purification device; Alternatively, the thickness of the niobium and hafnium alloy sheet is 0.1 to 2 mm, the distance between the niobium and hafnium alloy sheet and the dust collecting electrode in the high-voltage electrostatic air purification device is 15 to 200 mm; the niobium and hafnium alloy sheet is connected to the positive or negative electrode of the high-voltage electrostatic power supply in the high-voltage electrostatic air purification device.

8. The application of niobium-hafnium alloy material according to claim 5, characterized in that: The niobium-hafnium alloy material is used as a discharge electrode in the high-voltage electrostatic air purification device or the high-voltage electrostatic air purification component in the fresh air system in the form of niobium-hafnium alloy needles.

9. The application of the niobium-hafnium alloy material according to claim 8, characterized in that: The diameter of the niobium-hafnium alloy needle is ≤0.6mm, the distance between the niobium-hafnium alloy sheet and the dust collecting electrode in the high-voltage electrostatic air purification device is 15-200mm; the niobium-hafnium alloy needle is connected to the positive or negative electrode of the high-voltage electrostatic power supply in the high-voltage electrostatic air purification device.

10. The use of niobium-hafnium alloy material according to claim 6 or 7, characterized in that: The angle between the niobium-hafnium alloy wire or sheet and the dust collecting electrode in the high-voltage electrostatic air purification device is 0 to 90 degrees.

Citation Information

Cited By

  • Hafnium foil for electric vacuum device and preparation method of hafnium foil

    CN121802258A